Effect of in-season calcium applications on cell wall physicochemical properties of nectarine fruit (Prunus persica var. nectarina Ait. Maxim) after harvest or cold storage - Vasilakakis, Miltiadis; Diamantidis, Grigorios; Mignani, Ilaria; Manganaris, George A. (My University, 2006)
Pre-harvest calcium sprays with calcium chloride or with a commercial chelated calcium form at equivalent calcium rate were applied in nectarine trees at weekly intervals beginning 4 or 8 weeks before harvest, respectively. The fruits were harvested at commercial maturity stage and cold stored (0 °C, 95% RH) for 0, 2, 4 and 6 weeks, prior to their ripening at room temperature (20 °C) for 1 and 5 days. The interrelations between calcium content (total, cell wall and pectin-bound), cell wall components (polyuronide, neutral sugar and cellulose content) and tissue firmness of the nectarine fruits were examined. The two strategies (four or eight calcium sprays) were equally effective at increasing the fruit calcium content. Calcium increased by 14-25% in the peel and by 8-11% in the flesh, whereas cell wall calcium increased by 7-17% in calcium-sprayed compared to non-sprayed fruits after harvest. Cell wall and pectin calcium increased with the increase of storage time both in sprayed and non-sprayed fruits without a corresponding increase of total calcium and uronic acid content, indicating the formation of more sites for calcium binding as storage period increased. Neutral sugar and cellulose content remained unaffected by the application of calcium sprays.
Keywords: Nectarine; Calcium; Leaf sprays; Pectin; Cell wall; Tissue firmness